Sol-gel science : the physics and chemistry of sol-gel processing - Brinker, C. Jeffrey; Scherer, George W. (Boston : Academic Press, 1990)
Presents the physical and chemcial principles of the sol-gel process of ceramic preparation, at a level suitable for graduate students and practitioners in the field.
Includes bibliographical references and index.
Keywords: Ceramic materials; Colloids; Sol-gel processes; Ceramics; Gelation